A prospective study of pattern of prescription for acne vulgaris in a tertiary care hospital: an observational study - T., Nandini; Kumbar, Shivaprasad Kalakappa; S., Padmanabha T.; Krishna, Purushotham; G., Narendra (International Journal of Basic & Clinical Pharmacology, 2016)
Background: Acne vulgaris is a common dermatological disorder of the pilosebaceous unit affecting younger age groups but presenting usually at puberty and is of cosmetic concern. There are various treatment modalities available ranging from topical/oral anti-acne preparations to hormonal therapy depending on the severity of acne. Use of synthetic retinoid is highly regulated due to its potential for severe adverse events, primarily teratogenicity. There is a need for periodic prescription auditing. By providing feedback to the prescribers to formulate the guidelines enhances therapeutic efficacy by rational use, minimizes the adverse effects and cost of treatment. Objectives: to assess the prescription pattern for Acne vulgaris. Methods: A medication details and prescribers information are collected in pre-designed proforma along with the demographic details from 210 study subjects after personal briefing about the study. The data was analyzed using SPSS. Results: Out of 210 prescriptions of acne patients, majority were in between 21-40 years (48.09%), M:F ratio was1:1.41, female were 58.57% when compared to males 41.43%. Topical agents accounted for 54.13% and 36.36% of oral antibiotics (most common was azithromycin). Fixed dose combinations accounted for 4.39% and concomitantly administered drugs (antihistaminics, proton pump inhibitors, H2 blockers, emollients and skin protective agents) accounted for 53.82% of the prescribed drugs. Conclusions: Drug utilization study periodically can be an eye opener for the prescribers to prescribe the drugs in a rational way and it could reduce the prescription error and minimizing the untoward effects will subsequently reduce the cost of treatment.